Bioremediation of red azo dye from aqueous solutions by Aspergillus niger strain isolated from textile wastewater. Issue 1 (February 2017) - Mahmoud, Mohamed S.; Mostafa, Mohamed K.; Mohamed, Samah A.; Sobhy, Neama A.; Nasr, Mahmoud
Abstract: Biological treatment with fungi has proven to be effective in removing color from textile wastewater containing organic contaminants as an eco-friendly established technique. The main purpose of this research is to remove red azo dye from aqueous solution using Aspergillus niger strain. In a direct application, fungal biomass was tested for the decolorization under different environmental conditions such as contact time, bio-sorbent dosage, pH, agitation speed, and initial dye concentration. The highest azo dye removal efficiency was obtained at the pH 9, agitation speed 250, biosorbent dose 3.5 g, and contact time 120 min. The removal efficiency decreased with the increase in initial dye concentration. Freundlich isotherm model was best fitted when compared to Langmuir isotherm model, as it has a higher correlation coefficient (R 2 = 0.977). At dye concentration 1000 mg/L, the net dry biomass of A. niger increased from 0.18 to 0.58 g after seven days of incubation at 28 ± 1 °C indicating the high biodegradability of fungal strain. Examination with Scanning Electron Microscope (SEM) showed high affinity of A. niger to the direct red azo dye. The statistical analysis using the interactive response surface methodology (IRSM) technique showed that the dye removal efficiency depends mainly on the contact time, pH, and biomass dosage. In contrast, the effect of initial dye concentration and agitation speed on the dye removal was minor.